2015
DOI: 10.1002/pmic.201500079
|View full text |Cite
|
Sign up to set email alerts
|

Metaproteomics of aquatic microbial communities in a deep and stratified estuary

Abstract: Here we harnessed the power of metaproteomics to assess the metabolic diversity and function of stratified aquatic microbial communities in the deep and expansive Lower St. Lawrence Estuary, located in eastern Canada. Vertical profiling of the microbial communities through the stratified water column revealed differences in metabolic lifestyles and in carbon and nitrogen processing pathways. In productive surface waters, we identified heterotrophic populations involved in the processing of high and low molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
3
21
0
Order By: Relevance
“…Moreover, hexulose-6-phosphate synthase, the key enzyme of the RuMP pathway of OM43, is also detected in all Atlantic Ocean samples. In addition, methanol oxidation proteins originating from the common OM43 marine clade are also identified in a deep and stratified estuary [50]. These results support the in situ activities of the OM43 clade using one-carbon compounds for energy production.…”
Section: Microbial Community Proteomics In Various Environmentssupporting
confidence: 54%
“…Moreover, hexulose-6-phosphate synthase, the key enzyme of the RuMP pathway of OM43, is also detected in all Atlantic Ocean samples. In addition, methanol oxidation proteins originating from the common OM43 marine clade are also identified in a deep and stratified estuary [50]. These results support the in situ activities of the OM43 clade using one-carbon compounds for energy production.…”
Section: Microbial Community Proteomics In Various Environmentssupporting
confidence: 54%
“…These trends are in agreement with transmissivity values measured in situ, with values below 94% found in the surface waters of S18 and S22 or near the bottom of the LSLE stations (S20.5 and S22; Table ). The increase in turbidity near the bottom of the LSLE stations (S20.5 and S22) can be associated with the presence of a nepheloid layer (Colatriano et al ). This nepheloid layer might be absent or thinner (i.e., below the deepest sampling depth) at S18 in the GSL.…”
Section: Resultsmentioning
confidence: 99%
“…Although the presence of microbial OM near the water–sediment interface of the LSLE is clear, the strong increase in THAA concentrations and yields in this zone is probably not caused by a particularly intense bacterial production. A recent study of aquatic microbial communities in the LSLE (at a station between S20.5 and S22) revealed that the nepheloid layer is characterized by lower bacterial abundance and bacterial productivity compared to surface waters (2 and 39 times lower, respectively; Colatriano et al ). The accumulation of AA and bacterial molecules in the nepheloid layer of the LSLE is thus likely caused by another factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this phylum have been detected in the field and are basically related to marine chemolithotrophic nitrification (Pachiadaki et al., ). Nitrospina ‐like bacteria have been detected from the surface down to the deep ocean (DeLong et al., ; Nunoura et al., ; Santoro, Casciotti, & Francis, ; Watson & Waterbury, ) including in oxygen minimum zones (OMZs) (Beman, Shih, & Popp, ; Fuchsman, Kirkpatrick, Brazelton, Murray, & Staley, ; Labrenz, Jost, & Jurgens, ; Zaikova et al., ), oxic/anoxic sediments (Davis, Stakes, Wheat, & Moyer, ; Jorgensen et al., ; Rani, Koh, Rhee, Fujitani, & Park, ), and deep estuarine environments (Colatriano et al., ). These bacteria reach abundances as high as 9.25% of total 16S‐rRNA gene sequences recovered in bacterial sequence libraries obtained from the eastern tropical North Pacific (Beman et al., ), and up to one‐third of the bacterial 16S‐rRNA gene sequences in deep hypersaline ponds in the Red Sea (Ngugi, Blom, Stepanauskas, & Stingl, ).…”
Section: Introductionmentioning
confidence: 99%